Spt5 orchestrates cryptic transcript suppression and transcriptional directionality - Haejin An; Hyeokjun Yang; Daeyoup Lee (Communications Biology)
Abstract Spt5 is a well-conserved factor that manipulates multiple stages of transcription from promoter-proximal pausing (PPP) to termination. Recent studies have revealed an unexpected increase of antisense transcripts near promoters in cells expressing mutant Spt5. Here, we identify Spt5p-restricted intragenic antisense transcripts and their close relationship with sense transcription in yeast. We confirm that Spt5 CTR phosphorylation is also important to retain Spt5’s facility to regulate antisense transcription. The genes whose antisense transcription is strongly suppressed by Spt5p share strong endogenous sense transcription and weak antisense transcription, and this pattern is conserved in humans. Mechanistically, we found that Spt5p depletion increased histone acetylation to initiate intragenic antisense transcription by altering chromatin structure. We additionally identified termination factors that appear to be involved in the ability of Spt5p to restrict antisense transcription. By unveiling a new role of Spt5 in finely balancing the bidirectionality of transcription, we demonstrate that Spt5-mediated suppression of DSIF complex regulated-unstable transcripts (DUTs) is essential to sustain the accurate transcription by RNA polymerase II.